Investigation into authorized public data operation: its positioning and nature - Feng GAO (大数据)
At present, the theory and practice of authorized data operation are still chaotic and controversial.Based on the clarification of what open data means in the Chinese context, the current theory that authorized data operation is either complementary to open data or part of open data was challenged, and authorized data operation that implemented open data through a market-oriented delegation mechanism was repositioned.The need was presented to unpack the definitions of two key elements of authorized data operation: data product and data operation, and a novel interpretation of authorized data operation was proposed as it was a social-technical system serving the purpose of open data and mainly producing primary data products for reuse rather than just using with support from a rich tiered data operation service ecosystem.